Sugarcane Leaf Tissue Sample Preparation for Diagnostic Analysis - Ike V. Ezenwa; J. Mabry McCray; Peter R. Newman; Ronald W. Rice (EDIS, 2005)
This document focuses on sugarcane leaf tissue sampling for the purpose of foliar nutrient analysis and interpretation. This document is SS-AGR-259, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date November 2005.